2006
DOI: 10.1516/39m7-h9ce-5lqx-yegy
|View full text |Cite
|
Sign up to set email alerts
|

Implicit memory and early unrepressed unconscious: Their role in the therapeutic process (How the neurosciences can contribute to psychoanalysis)

Abstract: The author discusses memory from the point of view of the neurosciences and molecular biology, proposing an integration with the psychoanalytic theory of the unconscious. The discovery of the implicit memory has extended the concept of the unconscious and supports the hypothesis that this is where the emotional and affective--sometimes traumatic--presymbolic and preverbal experiences of the primary mother-infant relations are stored. They could form the ground structure of an early unrepressed unconscious nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 48 publications
2
55
0
3
Order By: Relevance
“…Indeed, there must be room to appreciate apperception apart from comprehension. Mancia (2006) has suggested that the implicit self exists in an unrepressed state, likely residing in more primitive sections of the brain that have been identified with core affect states, such as the amygdala, cerebellum, and temporo-occipito-parietal areas of the right hemisphere. In a review of the neuropsychology of spiritual experiences, Newberg and Newberg (2005) also implicated several other nonconscious systems, such as the interactive processes between prefrontal and cingulate cortexes, thalamic activation, hippocampal and amygdalar activation, hypothalamus, changes in the autonomic nervous systems, PSPL deafferentation, and serotonergic activity.…”
Section: Beyond Winnicott: the Foundational Affective Environment Of mentioning
confidence: 99%
“…Indeed, there must be room to appreciate apperception apart from comprehension. Mancia (2006) has suggested that the implicit self exists in an unrepressed state, likely residing in more primitive sections of the brain that have been identified with core affect states, such as the amygdala, cerebellum, and temporo-occipito-parietal areas of the right hemisphere. In a review of the neuropsychology of spiritual experiences, Newberg and Newberg (2005) also implicated several other nonconscious systems, such as the interactive processes between prefrontal and cingulate cortexes, thalamic activation, hippocampal and amygdalar activation, hypothalamus, changes in the autonomic nervous systems, PSPL deafferentation, and serotonergic activity.…”
Section: Beyond Winnicott: the Foundational Affective Environment Of mentioning
confidence: 99%
“…The theory I shall recapitulate here some concepts I have already partly elaborated (Mancia, 2003a(Mancia, , 2004(Mancia, , 2006a, resulting from neuroscientific observations on the functions of the memory and the unconscious, and on studies of mothers and children in relation to attachment (Bowlby, 1969), reflective functions (Fonagy & Target, 1997), and the organization of the self (Stern, 1985).…”
Section: Implicit Memory and Early Unrepressed Unconsciousmentioning
confidence: 99%
“…Therefore, in the preverbal and presymbolic stages of life, when the mother and child identify with each other, using protolinguistic forms of communication, sharing affective states, and enjoying a relational state in which inter-subjectivity implies inter-fantasy, the infant will be able to set up affective representations and store them in implicit memory. These will form the unrepressed unconscious structure of his mind (Mancia, 2003a(Mancia, , 2004(Mancia, , 2006a, taking us back to Freud's idea (1915b, p. 195) that ''the content of the Ucs. may be compared with an aboriginal population in the mind.…”
Section: Implicit Memory and Early Unrepressed Unconsciousmentioning
confidence: 99%
“…As an example of therapeutic "upward causation," the integration of psychoanalytic psychotherapy with psychoanalytic movement therapy can evoke a "day precipitate" (Kelman, 1975) of subsequent latent dream themes and their symbolic imagery, long before the "putting into words" has occurred (Ragan & Seides, 1990). In such work, the enactment in the movement therapy serves as a prototypical "waking dream" (Kern, 1987), anticipating the more symbolic and higher level dream content and dream work (Mancia, 2006;Ragan & Seides, 1990). Miyashita's concept of "event (episodic) memory" may be akin to Schore's and Olds's concept of "procedural memory," which Ragan and Seides (1990) have linked to the concept of "muscle memory" and the "psychosomatic potential space.…”
mentioning
confidence: 99%
“…The "muscle memory" concept could be easily linked to the cognitive neuroscience research on "implicit memory" (a.k.a., "non-declarative memory"; Schacter, 1995;Squire, 1994), which subsumes procedural memory and emotive/affective memory, whose organization is developmentally first overseen by the infantile amygdala, basal ganglia, and cerebellum for the storage and retrieval of preverbal experiences (Mancia, 2006). Recent studies by Stickgold, Malia, Maguire, Roddenberry, and O'Connor (2000) on the sequelae of loss of "explicit memory" (or "declarative memory" for events) from lesions to the bilateral temporal lobe and hippocampus, showed that learning and dream representation of what was learned could still be accomplished "without the contribution of explicit memory, which requires the activation of the hippocampus and of the temporal and basal cortex" (Mancia, 2006, p. 85).…”
mentioning
confidence: 99%